Effect Of Online Tracking System And Delivery Timeliness On Customer Satisfaction (Case Study On J & T Express Sampit) - Oetama, Seanewati; Susanto, Hari; Rizwannur, Wahyu (Publisher Cv. Inara, 2024)
The title of this study is the effect of Online tracking system and Keteptan delivery time on customer satisfaction (Case Study on J&T Express Sampit). This study was conducted at J & T Express Sampit which is located at Jalan MT. Haryono No. 095, Mentawa Baru Hulu, District. Mentawa Baru Ketapang, East Kotawaringin Regency, Central Kalimantan. This study was conducted on customers who use the services of J & T Express Sampit with accidental sampling technique. And the data were tested using validity test, reliability test, hypothesis test and analysis of research data using descriptive analysis, multiple linear regression analysis, correlation coefficient analysis and determination analysis. Based on the results of the hypothesis test in this study is a T-test for online tracking system variables (X1) IE t count 3.146 > t table 2.00324 and a significant level of 0.001 < 0.05 then H0 rejected and Ha accepted. This means that there is a significant influence of Online tracking systems on customer satisfaction. As for the T-test for variable timeliness of delivery (X2) is t count 4.763 > t table 2.00324 and a significant level of 0.000 < 0.05 then H0 rejected and Ha accepted. This means that there is a significant influence between the timeliness of delivery to customer satisfaction. Then for the F-test, namely F count 25.098 > F table 3.16 and a significant level of 0.000 < 0.05 means that simultaneously the Online tracking system and delivery timeliness have a significant effect on customer satisfaction. R number of 0.690 shows the relationship / correlation between customer satisfaction with the independent variable is strong (significant). Adjust R Square of 0.552 means that 55.20% of customer satisfaction variable (Y) can be explained by Online Tracking System variables (X1) and delivery timeliness (X2). While the remaining 44.8% were influenced by other variables that were not included in this study. Based on the results of multiple linear regression test obtained by the equation Y = 1.233+ 0.407 (X1) + 0.580 (X2) means that the score/value of the constant ( ? ) shows that if there is no increase in the variables of the online tracking system and the accuracy of delivery time then the value of customer satisfaction is equal to 1.233. And each addition of one score / variable value of the online tracking system provides an increase of 0.407 to customer satisfaction with fixed X2 conditions and each addition of one score/variable value of delivery timeliness provides the same increase of 0.580 to customer satisfaction with fixed X1.